Translation Techniques of Indonesian Subtitle in Our Planet Documentary Series - Mega Tri Utami; Nisrina Satyaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2022)
In Indonesia, the screening of Our Planet documentary which has been translated into Indonesian was carried out by The Ministry of Education and Culture of the Republic of Indonesia, in collaboration with Netflix starting on June 20, 2020. This collaboration is a manifestation of the Study from Home program. Indonesia's flora, fauna and nature are also part of this documentary. The original language of the documentary is English, and there could be meaning differences in the Indonesian subtitle. The researchers are interested to know about the translation strategies and techniques in translating the subtitles for Our Planet documentary series in maintaining the same meaning as SL. Molina and Albir’s theory which consists of 18 translation techniques was used in this study. The study utilizes a descriptive qualitative method that requires Our Planet’s subtitle transcription both in English (as SL) and Indonesian (as TL) as its data source. The researchers discovered 14 translation techniques, which include established equivalent techniques that have become the most commonly used technique, accounting for 50.6 percent of all techniques used. The description and modulation technique have the lowest percentage, at only 0.6 percent.